Interaction between cetylpyridinium chloride and amino acids: A conductomertic and computational method study. Issue 11 (2nd November 2017) - Hoque, Md. Anamul; Patoary, Mohammad-Omar-Faruk; Molla, Mohammad Robel; Halim, Mohammad A.; Khan, Mohammed Abdullah; Rub, Malik Abdul
ABSTRACT: Herein, we have investigated the interaction between three different amino acids (AA) namely glycine (Gly), threonine (Thr), and alanine (Ala) with cationic surfactant cetylpyridinium chloride (CPC) by conductance measurements and computational method. For pure CPC as well as amino acid–CPC mixtures, three different critical micelle concentrations ( c *) were achieved. The values of c * for the AA–CPC mixtures in KCl solution are lesser in comparison to the aqueous solution. The negative values of are obtained in every studied system. The values of and for AA–CPC micellization reveal that both hydrophobic and hydrophilic interactions are the binding forces among CPC molecules and between AA and CPC. Molecular dynamics simulation indicates that the pyridine ring of CPC promotes the non-bonding interaction in AA–CPC complexes. Further quantum calculation revealed that non-conventional CH⋯O hydrogen bonding plays a critical role and stabilizes these complexes. GRAPHICAL ABSTRACT: